An analysis of historical wind-driven rain loads for selected Canadian cities. Issue 213 (June 2021) - Xiao, Zhe; Lacasse, Michael A.; Dragomirescu, Elena
Abstract: The performance and durability of wall assemblies are greatly affected by the moisture load to which they may be subjected, in particular those arising from Wind-Driven Rain (WDR). Standard approaches for estimating such moisture loads assume 1% of the WDR load, whereas these loads have also been assessed from watertightness tests, although these assumed loads have been determined based on limited climate information. To more accurately estimate the moisture loads to which wall assemblies may be subjected over their service life, an analysis of historical WDR loads was completed for 11 cities across Canada. The magnitude, probability of occurrence of WDR loads in different cities and correlations between WDR related climate parameters, are discussed in this paper. Also, a novel WDR severity index is introduced, referred to as the Wind-Driven Rain Pressure Index, to permit quantifying the real-time and simultaneously occurring effects of WDR intensity and Driving Rain Wind Pressure (DRWP). To estimate the WDR intensity and DRWP with a specific probability of occurrence, an Extreme Value Analysis (EVA) was completed for a climate dataset of 31 years (1986–2016) using the Generalized Extreme Value and Gumbel distributions. Highlights: There is no correlation between the Wind-Driven Rain (WDR) load and concurrent Driving Rain Wind Pressure (DRWP). A novel Wind-Driven Rain Pressure Index (WDRPI) is proposed. Current watertightness test protocols are not reflecting most of the WDR conditions. Gumbel distribution is a better option to generate the Intensity-Duration-Frequency curve for the WDR and WDRPI. WDR conditions in different cities varies greatly.